The relationship between teachers' knowledge and beliefs about inquiry and their classroom practices - Saad, Rayana Fouad (Beirut American University of Beirut. Faculty of Arts and Sciences, 2008)
The purpose of this study was to investigate the relationship between teachers' knowledge and beliefs about inquiry and their classroom teaching practices in middle and high school science classes. Specifically, the study attempted to answer the following questions: (1) What are teachers' beliefs and knowledge about inquiry? (2) What are teachers' teaching related classroom practices? (3) Do teachers' knowledge and beliefs about inquiry relate to their science classroom practices? The study sample was drawn from schools in the City of Beirut. To answer the first question, teachers were asked to fill out two questionnaires, one open-ended and another of the Likert-type, that gauge their beliefs and knowledge about inquiry. To answer the second question, classroom observations were conducted to document actual teaching strategies. Frequencies and descriptive statistics were generated from the data collected in the Likert-type questionnaire and were used to construct profiles for each of the teachers based on their knowledge and beliefs about inquiry. Data from the open-ended questionnaire were used to validate characteristics of the profiles. Consequently, teachers were categorized based on their profiles. Data from observations were used to characterize each of the teachers' classroom teaching practices. Finally, to answer the third question, teachers' profiles and classroom practices were investigated to identify relationships between teachers' beliefs and knowledge and their teaching practices. Results showed that most teachers had restricted views of the nature of science and had unfavorable beliefs and attitudes about inquiry. Moreover, there did not seem to be a relationship between teachers' beliefs, views of the nature of science, and their classroom practices.
: Mémoire
Keywords: Class Management; Gestion d une classe; Les Attitudes et conceptions des enseignants; Nature de la science; Nature of Science; Teachers attitudes and conceptions